Re-discovery and Re-description of Ansonia penangensis Stoliczka, 1870 (Anura: Bufonidae) from Penang Island, Malaysia - H., Evan Quah S.; Grismer, L. Lee; Muin, Mohd Abdul; M.s., Shahrul Anuar (Zootaxa, 2011)
Ansonia penangensis Stocliczka 1870 is re-discovered from its type locality in Penang Hill from Penang Island, Malaysia after more than a century. The species was previously known only from the type series; two adults and a larval series collected in 1898, and had not been recorded since. An expanded description of this species is provided, based on four recently acquired specimens and corroborate the morphological differences between Ansonia penangensis, A. malayana and A. jeetsukumarani, with which A. penangensis has been confused.